The Longest August : The Unflinching Rivalry Between India and Pakistan - Hiro, Dilip (New York Nation Books, 2015)
A sweeping account of the relationship between Pakistan and India that traces the two countries' contentious history from long simmering tensions between Hindus and Muslims, to the conflict over Kashmir, to the possibility for a present day detente.
Include Maps, Notes, Bibliography and Index
Keywords: POLITICAL SCIENCE -- Government -- International. -- Pakistan -- Foreign relations -- India. -- India -- Foreign relations -- Pakistan. -- Diplomatic relations